Subclinical Hepatic Encephalopathy in Cirrhotic Patients: Prevalence and Relationship to Liver Function - Gilles Pomier-Layrargues; Ngoc Huu Nguyen; Claire Faucher; Jean-François Giguère; Roger F Butterworth (Canadian Journal of Gastroenterology)
Neuropsychological tests were administered to 22 alcoholic cirrhotic patients, 20 nonalcoholic cirrhotic patients and 42 control subjects matched for age and educational background. Liver function estimated by Pugh score was identical in alcoholic and nonalcoholic cirrhotics. Thirty-two cirrhotic patients (76%) failed one or more psycho logical test. Performance was worse in cirrhotics than in controls in all but one test: the degree of neurological impairment was similar in alcoholics and nonalcoholics and correlation with the severity of Liver dysfunction was only marginal. A combination of the five more sensitive tests was able to identify 31 of 32 cirrhotic patients with subclinical encephalopathy; this ‘mini battery’ of tests can be performed within 10 mins. Suhclinical hepatic encephalopathy is frequent in cirrhotic patients and can adversely affect their psychosocial behaviour.